2012
DOI: 10.1186/1741-7007-10-55
|View full text |Cite
|
Sign up to set email alerts
|

Low level genome mistranslations deregulate the transcriptome and translatome and generate proteotoxic stress in yeast

Abstract: BackgroundOrganisms use highly accurate molecular processes to transcribe their genes and a variety of mRNA quality control and ribosome proofreading mechanisms to maintain intact the fidelity of genetic information flow. Despite this, low level gene translational errors induced by mutations and environmental factors cause neurodegeneration and premature death in mice and mitochondrial disorders in humans. Paradoxically, such errors can generate advantageous phenotypic diversity in fungi and bacteria through p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 102 publications
(108 reference statements)
2
42
1
1
Order By: Relevance
“…Decreases in fidelity are also undesirable: in the yeast Saccharomyces cerevisiae , the introduction of a transfer RNA that miscodes a leucine codon as serine results in the chronic mistranslation of the entire transcriptome 45 . This reduction in fidelity produces a transcriptional response that resembles the environmental stress response, as well as a decrease in ribosomal protein mRNAs, a decrease in the overall rates of protein synthesis and an overall reduction in fitness 45 . To survive, cells that have unstable genomes, such as cancer cells, might require compensatory adaptation to such prolonged activation of stress responses.…”
Section: Causes Of Proteome Imbalancementioning
confidence: 99%
“…Decreases in fidelity are also undesirable: in the yeast Saccharomyces cerevisiae , the introduction of a transfer RNA that miscodes a leucine codon as serine results in the chronic mistranslation of the entire transcriptome 45 . This reduction in fidelity produces a transcriptional response that resembles the environmental stress response, as well as a decrease in ribosomal protein mRNAs, a decrease in the overall rates of protein synthesis and an overall reduction in fitness 45 . To survive, cells that have unstable genomes, such as cancer cells, might require compensatory adaptation to such prolonged activation of stress responses.…”
Section: Causes Of Proteome Imbalancementioning
confidence: 99%
“…For the cell, the consequences of aaRSs failing to discriminate between amino acids is potentially disastrous and could lead to mistranslation of proteins and activation of cellular stress responses 16 . The challenge to correctly recognize the 20 proteinogenic amino acids centres around their limited diversity in chemical space, which makes it difficult to accurately select substrates from a pool of structurally similar constituents 17 .…”
Section: Mechanisms Of Translational Fidelity and Errormentioning
confidence: 99%
“…Paredes et al studied the global effects of substituting serine for leucine—which have comparable amino acid hydrophobicity ranks to tyrosine and phenylalanine, respectively—and showed that even a low level of amino acid mistranslation that does not affect growth rate in yeast (~1%) is sufficient to up-regulate genes associated with oxidative stress, ER stress, and heat shock while down-regulating genes related to protein synthesis. At the same time the enzymatic activity of specific proteins was reduced, and protein aggregation increased (Paredes et al, 2012). It is therefore possible that the resulting substitution of a polar tyrosine isomer for non-polar phenylalanine during protein synthesis produces adverse changes to protein structure and activity and elicits various downstream cellular response pathways, including activation of the unfolded protein response, the heat shock response, augmented proteasome activity, and/or promotion of apoptosis.…”
Section: Potential Mechanisms For the Adverse Effects Of M- And O-mentioning
confidence: 99%